Table of Content - - (Journal of natural sciences, life and applied sciences, 2024)
Table of Content: 1. Water erosion and the vulnerability of ecological balances; The case of the lower part of Oued Za basin (Eastern Morocco) Dr. BENHAMED Abderrahim, PES. SBAI Abdelkader 2. The impact of changes in temperature trends on relative humidity trends in the city of Jeddah in Kingdom of Saudi Arabia for the period from 1985 to 2022 AD Mrs. Jamila Awad Al-Anazy, Co-Prof. Lameah Abed Al-Aziz Al-Jasser 3. Evaluating the change in vegetation cover in the city of Buraidah in the period from 2014 to 2024 Using geographic information systems and remote sensing: A case study of Qassim National Park Mrs. Samiayh Suliman Aleairi 4. Thin Film Biosynthesis of Zinc Oxide Nanoparticles Using Thymus Serpyllum Plant Extract Dr. Rasha Hosam Saleh